The Pharmaceutical Sector in Ghana - Seiter, Andreas (World Bank, Washington, DC, 2017)
Main pharmaceutical policy goals in Ghana are access to essential medicines for everybody, quality assurance for all drugs on the market, a functioning and efficient supply chain as well as rational use of medicines by professionals and patients. There is also a commitment to strengthen the domestic pharmaceutical industry, outlined under health industry in the national health policy. The National Health Insurance System (NHIS) has significantly improved access to medicines for insured patients, measured in increased utilization of facilities and rapidly growing turnover of revolving drug funds. The risk is now that non-rational prescribing and fraud lead to a growing medicine bill that threatens financial sustainability of NHIS. On the other hand, National Health Insurance Authority (NHIA) has the resources and purchasing power to influence provider behavior as well as the market in terms of quality and price. The purpose of this policy note is to provide a compact overview of the situation, trends and opportunities in the pharmaceutical sector in Ghana as relevant to the strategic objectives in the five year program of work. It summarizes data from a number of recent studies and reports that were done by a range of partners inside and outside the country as well as discussions with key stakeholders in the sector. The intent is to give decision makers up-to-date background information and provide some suggestions for specific policy initiatives designed to achieve the work program objectives, with a particular focus on the role health insurance can play to stabilize and improve service delivery, increase access to quality medicines and promote rational use. The overall legal framework for the pharmaceutical sector is set by the Food and Drugs Law from 1992, amended by Act 523 in 1996. It defines the role of the food and drugs board as separate entity under control of the Ministry of Health (MOH), responsible for regulating the sector. The Food and Drugs Board (FDB) also runs the official drug quality control laboratory that is in charge of testing quality samples obtained from manufacturers, importers, distributors or other sources. The FDB is also working on an improvement of its public website in an effort to strengthen communication with the general public to increase transparency and improve governance.